Advancing agricultural economic growth through technology innovation and structural transformation: A multilevel analysis - Chenggang Li; Cong Luo; Hongye Jia; Mu Yue; Liang Wu (Journal of Innovation & Knowledge (JIK), 2025)
The agricultural economy plays an irreplaceable and crucial role in ensuring national food security, promoting stable economic growth, and fostering harmonious social development. Agricultural technology innovation (ATI) and rural industrial structure transformation (RIST) are key drivers of agricultural economic growth (AEG). Although previous studies have largely focused on the individual impacts of ATI and RIST on AEG, research on the specific pathways linking these factors is limited. This study utilizes panel data from 30 Chinese provinces from 2009 to 2022 and employs a multilayer structural equation model to systematically examine the relationships among ATI, RIST, and AEG at both national and regional levels. In addition, it provides an in-depth analysis of the internal connections among specific variables. The findings indicate that, at the national level, ATI plays a crucial role in significantly advancing both the transformation and upgrading of rural industrial structures and AEG. However, the direct impact of RIST and upgrading on AEG is not clearly evident. The regional-level analysis reveals that ATI has a significant positive effect on AEG and promotes the optimization of rural industrial structures. In addition, upgrading rural industrial structures significantly enhance AEG. This study's methodology offers both theoretical and empirical support for promoting agricultural economic development through ATI and RIST upgrading. The findings provide valuable insights for policymakers, enabling them to better align agricultural policies with key innovation directions and structural improvements, ultimately fostering sustainable agricultural development. Furthermore, the conclusions serve as a decision-making reference for agricultural enterprises and practitioners, guiding them to adapt to industrial structural adjustments, leverage technological advancements, and enhance agricultural production efficiency and economic benefits.
Keywords: Q16; Q55; O13; 650; Agricultural economic growth; Agricultural technology innovation; Multilevel structural equation model; Rural industrial structure transformation